The Influence of Price, Promotion, Location, and Facilities on Parental Decision-Making in Choosing MTs Darussalam Kemiri, Batang Regency, Central Java - Hasanah, Silvi Nadiyatul; Machali, Imam (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2025)
Purpose – This study aims to analyze the influence of price, promotion, location, and facilities on parents’ decision to enroll their children at MTs Darussalam Kemiri, Subah District, Batang Regency, Central Java. Design/methods – The research employed a quantitative approach with survey methods. Data were collected through questionnaires distributed to parents of students, and the analysis was conducted using multiple linear regression to examine the effect of the independent variables on parents’ decision-making. Findings – The results indicate that price, promotion, location, and facilities significantly influence parents’ decision to choose MTs Darussalam Kemiri. Among these, facilities emerged as the most dominant factor shaping parental choice, while the other variables also contributed positively. Research implications/limitations – The study was limited to one school in a single region, which constrains the generalizability of the findings. Future studies should expand the scope by comparing multiple institutions or regions to capture broader determinants of school choice. Practical implications – The findings provide valuable insights for educational institutions in developing effective strategies to attract students. Schools should prioritize improving infrastructure and facilities, while also maintaining competitive tuition pricing, targeted promotions, and strategic location considerations. Originality/value – This research contributes to the limited body of literature on parental school choice in the Indonesian Islamic education context, particularly highlighting the combined role of price, promotion, location, and facilities in influencing decision-making.